PENDIDIKAN SYUKUR MENURUT AL-QUR’AN - Sulastri, Sulastri (Moderation | Journal of Islamic Studies Review, 2023)
The context of Gratitude in religious studies is very emphasized, it has even become a field of da'wah and part of practice in life, but in the context of education there are still not many who develop it, especially the lack of legal excavation with the perspective of the Qur'an. This article uses a library research review using library data (primary sources and secondary data). Primary data are sourced from verses of the Qur'an which are the object of research. The author's secondary data sources refer to literature data, one of which is a book entitled: Insights of the Qur'an, by M. Quraish Shihab as the main reference, in addition to referring to scientific works in the form of: journals, theses, theses and dissertations that are credible and can support research improvement.